KOMBINASI PEMBERIAN AROMATERAPI LAVENDER DAN BRAIN GYM TERHADAP TINGKAT STRESS MAHASISWA PROGRAM STUDI DIPLOMA III KEBIDANAN PALU JURUSAN KEBIDANAN POLTEKKES KEMENKES PALU: THE COMBINATION OF LAVENDER AROMATERAPY AND BRAIN GYM ON THE LEVEL OF STUDENTS 'STRESS DIPLOMA III STUDY PROGRAM PALU MIDWIFERY DEPARTMENT POLTEKKES KEMENKES PALU - Widyayanti, Asri; Nita, Niluh (Viva Medika, 2021)
Stress can be felt by adults or during college age. The stress experienced by students on activities, situations on campus such as theory exams, practical exams, assignments from lecturers, extracurricular activities. Methods for dealing with stress such as relaxation, music therapy, Lavender aromatherapy, Brain Gym and exercise. The purpose of this study was to determine the effect of a combination of lavender aromatherapy and Brain Gym on the stress level of students of Palu Midwifery Diploma III Department of Midwifery, Health Ministry of Health, Palu. The research design used a quasy experimental method with one group pre-post test without control design, cross sectional approach. This research has been carried out in the Study Classroom of D-III Midwifery Study Program Students in Palu level II semester III for three weeks (21 October to 8 November 2019). The population and sample in this study were all students of the Diploma III Midwifery Study Program Palu level II semester III totaling 77 students. The sampling technique in this study is by means of the total population. Obtained an average stress reduction before and after the study was -10.04 (3.65). The mean rank score is 38,50. The results of statistical tests show p value <0.001 which indicates that the alternative hypothesis is accepted and null hypothesis is rejected. This means that there is an effect of the combination of lavender aromatherapy and Brain Gym on student stress levels. The conclusion is that there is an effect of the combination of lavender aromatherapy and Brain Gym on student stress levels. Suggestion: students should still maintain their ability to adapt to the campus situation. There is an active role of lecturers at the academic level and psychological approach. Lecturers are willing to be a place for sharing or discussion for students. Keywords: Lavender Aromatherapy, Brain Gym, Student